The ASSESSMENT OF THE STATE OF THE WATER ECOSYSTEMS OF THE TERRITORIES OF THE TURKESTAN REGION AT THE LEVEL OF "ZERO BACKGROUND", LOCATED IN CLOSE PROXIMITY TO THE NUCLEAR POWER PLANT UNDER CONSTRUCTION IN UZBEKISTAN (Experimental biology, 2023)
The article describes the radiobiological state of open reservoirs, drinking water in the settlements of the Turkestan region, which are potentially affected by the nuclear power plant under construction in Uzbekistan, as well as some biota objects that can serve as indicator organisms. The relevance is due to the fact that the settlements of the Turkestan region of the Republic of Kazakhstan, located near the border with Uzbekistan, fall under the potential impact of the future nuclear power plant. The objects of the study were samples of drinking water from 5 settlements, bottom sediments and hydrobionts (pike-perch - Sander lucioperca), carp (Cyprinus carpi), lake frog (Pelophylax ridibundus), water samples taken from open reservoirs of the Turkestan region. On the basis of an accredited the test laboratory of radiochemistry and radiospectrometry of the Institute of Radiobiology and Radiation Protection conducted tests on the content of radionuclides. The results obtained on the content of radionuclides at the stage of "zero background" before the construction of the nuclear power plant are generally within the normal range, with the exception of samples of drinking water from the village of Zhyly-su , where the total alpha activity exceeds 1.5 times the maximum allowable concentration. The results obtained will allow us to estimate the probable dose loads of the population from the intake of radionuclides through food chains and various scenarios. Data on the content of radionuclides in open water bodies and in drinking water will be used as one of the criteria, for a full assessment of the “zero pho on the territories of the Turkestan region.
Keywords: "zero background", drinking water, open reservoir, nuclear power plant, radionuclides